2014
DOI: 10.1075/scl.64
|View full text |Cite
|
Sign up to set email alerts
|

The (Ir)reversibility of English Binomials

Abstract: Amazon.com: The (Ir) reversibility of English Binomials: Corpus, constraints, developments (Studies in Corpus Linguistics) (9789027203724): Sandra Mollin: (Ir)reversibility of English Binomials Corpus, constraints, developments Building a large annotated Corpus of English: the Penn Treebank. A novel resource was required for this corpus-based research.. bow and arrow; Malkiel 1959), or the notion of irreversibility, i.e. the tendency of binomials to A link B. Our data analysis, which results in the constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 138 publications
1
30
0
Order By: Relevance
“…Instead, corpus analyses found that word order was strongly predicted by the words' semantic meaning (Benor & Levy, 2006;Mollin, 2014). Words signaling high power tended to be listed before less powerful referents (for a review, see Hegarty, 2015).…”
Section: Androcentric Behaviormentioning
confidence: 99%
“…Instead, corpus analyses found that word order was strongly predicted by the words' semantic meaning (Benor & Levy, 2006;Mollin, 2014). Words signaling high power tended to be listed before less powerful referents (for a review, see Hegarty, 2015).…”
Section: Androcentric Behaviormentioning
confidence: 99%
“…Intensifier canny was also judged as more frequent in predicative than attributive position, reflecting the distribution of intensifiers in real speech as reported in previous research. Therefore, just as the questionnaire participants gave judgements matching the age-related trends in DECTE, they were able to discern the linguistic distribution of intensifiers, demonstrating the correspondence between corpus data and speaker intuitions in this regard (Hoffmann 2006;Bresnan and Ford 2010;Mollin 2014). Judgements are therefore a valuable tool for accessing speaker intuitions about the functions of dialect forms, allowing researchers a window into the processes of grammaticalisation that incoming intensifiers undergo which cannot always be observed using vernacular speech corpora alone, particularly with low-frequency items that would be difficult to analyse reliably using multivariate techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The argument behind this is that high-frequency linguistic items and collocations have stronger and more accessible mental representations than low-frequency ones (Bybee 2007: 10). Studies comparing the frequency of syntactic phenomena and their linguistic constraints in corpus data with results from speaker intuitions have demonstrated remarkable correspondence between the two (Hoffmann 2006;Bresnan and Ford 2010;Mollin 2014). As such intuitions are "in all likelihood based on frequency information stored in the mental lexicon" (Mollin 2014: 212), the third hypothesis is that adjectives that are more frequent in speech overall will be perceived to occur with intensifier canny more than less frequent adjectives.…”
Section: Hypothesis 3: Adjective Frequencymentioning
confidence: 99%
“…There has been a lot of research and debate about the sequence of the elements and the factors that govern or influence this sequence [e.g. Malkiel (1959: 142-154); Mollin (2014)]. Several factors play a role; these can overlap and reinforce each other, but they can also contradict each other.…”
Section: Reasons For the Sequencementioning
confidence: 99%